2007
DOI: 10.1542/peds.2006-2221
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl)phthalate and Deep Venous Thrombosis in Children: A Clinical and Experimental Analysis

Abstract: Such occurrence of catheter-related deep venous thrombosis led to the assumption that disintegration of intravenous tubing resulted in intravenous administration of debris. Our data suggested that the particles derived from the tubing are of such size that they might induce catheter-related deep venous thrombosis. The absence of catheter-related deep venous thrombosis caused by the introduction of submicron inline filters outlines the important pathophysiological role of di-(2-ethylhexyl)phthalate-plasticized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Concern has been growing worldwide regarding the toxic potential of DEHP, which has been confirmed to cause thrombophlebitis. 12 The link between the incidence of infusion-related F Liu, D Chen, Y Liao et al Intrafix ® SafeSet reduces phlebitis in neurological ICU patients phlebitis and the type of infusion apparatus does, however, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Concern has been growing worldwide regarding the toxic potential of DEHP, which has been confirmed to cause thrombophlebitis. 12 The link between the incidence of infusion-related F Liu, D Chen, Y Liao et al Intrafix ® SafeSet reduces phlebitis in neurological ICU patients phlebitis and the type of infusion apparatus does, however, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…DEHP leaching has been reported to vary between 0.25–0.40 mg/100 mL/day for whole blood stored more than 21 days at 4°C, to 6 mg/unit of platelet concentrate stored at room temperature 25,27,28 . Furthermore, DEHP tubing has been shown to disintegrate with time, with one study measuring 6–12% less weight after product usage 29 , and another study reporting large particle debris from tubing degradation 30 . Of interest, both studies attributed medical complications to these findings.…”
Section: Di-2(ethylhexyl)phthalate (Dehp)mentioning
confidence: 99%
“…Some reports have indicated that DOP had adverse effects on the human body, especially for vulnerable individuals and with long‐term exposure. For instance, some diseases, including deep venous thrombosis, bronchopulmonary dysplasia, and cholestasis, are outcomes of exposure to DOP . The classification of DOP under Classification, Labeling, and Packaging regulation EC 1272/2008 is as a category 1B reproductive toxicant .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some diseases, including deep venous thrombosis, bronchopulmonary dysplasia, and cholestasis, are outcomes of exposure to DOP. [5][6][7][8] The classification of DOP under Classification, Labeling, and Packaging regulation EC 1272/2008 is as a category 1B reproductive toxicant. 9 Also, migration causes a loss of mechanical properties and makes the PVC brittle.…”
Section: Introductionmentioning
confidence: 99%